Pemikiran Akidah Moderat di Nusantara Abad ke-19 dalam naskah Qawā‘id Fawā‘id Fi Mā Lā Budda Min Al-‘Aqā‘id - Akhmad Munawwar (Jurnal Lektur Keagamaan, 2014)
Manuscript of Qawā‘īd Fawā‘īd (QF) kept in National Library is a theological manuscript embraced Asy’ariyah and Maturidiyah sects which tended to be more moderate than Khawarij and Mu’tazilah group. In its contents, this manuscript and also others defended the the purity of Islamic doctrine that is in line with Qur’an and Sunnah. Therefore, this reasearch opposes the arguments stated that Islam used and developed in Indonesia had been influenced by mistics from India and Persia. This research focuses on studying GF manuscript by elaborating any tendencies on theology developed in its term. Besides, this research also looks for red threat on how the relationship appeared among other manuscripts in term of theology. To analyse this manuscripts, this reasearch uses Philological and discourses analysis approach.Keywords: Texts, Islam, Theology, moderate, manuscript